Biological Risk Factors of Low Birth Weight in Rural Rajshahi - Ullah, MA; Haque, MJ; Hafez, MA; Khanam, Merina (TAJ: Journal of Teachers Association, 2009)
This prospective type of study was conducted in nine rural upazilas of Rajshahi district with a view to find out the biological risk factors of low birth weight (LBW). The calculated minimum required sample size was 748. A total 900 pregnant mothers in 3rd trimester were selected by two stage cluster sampling technique for follow up. Data were collected for 822 singleton live birth successfully and analyzed. Maternal weight < 50 kgs at 3rd trimester, birth interval < 2 years and female sex of the new born were identified as the important risk factors of LBW in rural community of Rajshahi district. Sex of the newborns is genetically determined, but maternal weight < 50kgs in third trimester and birth space < 2 years can prevented by measures like proper antenatal care, health & nutritional education, effective family planning services etc. doi: 10.3329/taj.v16i2.3881 TAJ December 2003; Vol.16(2): 50-53